Pemanfaatan Tiktok sebagai Sarana Dakwah bagi Mahasiswa KPI UNISBA - Devid Fernanda Hendy Ramadhan; Ida Afidah; Muhammad Fadhli Muttaqien (UPT Publikasi Ilmiah Unisba, 2026)
Abstract. This study aims to analyze the use of TikTok as a means of da'wah by students of the Islamic Broadcasting Communication (KPI) Study Program at Bandung Islamic University, class of 2021, and to identify the obstacles encountered in this process. The study used a qualitative approach with descriptive methods through questionnaires and structured interviews. Data analysis was based on Everett M. Rogers' Diffusion of Innovation Theory, specifically on aspects of innovation, communication channels, and social systems. The results showed that TikTok was used as a da'wah medium by the research subjects based on positive responses from interviews and positive results from questionnaires. However, there were obstacles in its use, including limited technical capabilities in content production, difficulties in simplifying da'wah materials, content consistency, and negative responses from some audiences. This study confirms that the use of digital da'wah media through TikTok by students of the Islamic Broadcasting Communication (KPI) Study Program at Bandung Islamic University, class of 2021 is good, although it is still greatly influenced by individual readiness, social environment, and time factors in accepting media innovations. Abstrak. Artikel ini bertujuan untuk menganalisis pemanfaatan media sosial TikTok sebagai sarana dakwah oleh mahasiswa Program Studi Komunikasi Penyiaran Islam (KPI) Universitas Islam Bandung angkatan 2021 serta mengidentifikasi kendala yang dihadapi dalam proses tersebut. Artikel menggunakan pendekatan kualitatif dengan metode deskriptif melalui kuesioner dan wawancara terstruktur. Analisis data didasarkan pada Teori Difusi Inovasi Everett M. Rogers, khususnya pada aspek inovasi, saluran komunikasi, dan sistem sosial. Hasil artikel menunjukkan bahwa TikTok dimanfaatkan sebagai media dakwah oleh subjek artikel berdasarkan respon positif dari wawancara dan hasil positif dari kuesioner namun terdapat kendala pemanfaatan berupa keterbatasan kemampuan teknis produksi konten, kesulitan menyederhanakan materi dakwah, konsistensi konten, serta respons negatif dari sebagian audiens. Artikel ini menegaskan bahwa pemanfaatan media dakwah digital melalui TikTok oleh mahasiswa Program Studi Komunikasi Penyiaran Islam (KPI) Universitas Islam Bandung angkatan 2021 sudah baik meskipun masih sangat dipengaruhi oleh kesiapan individu, lingkungan sosial, dan faktor waktu dalam menerima inovasi media.